Observation of Transition from Rate Law to Butler-Volmer Controlled Water Oxidation Kinetics on Hematite Photoanodes. - He,T; Benetti,D; Tseng,C; Moss,B; Teschner,D; Jones,TE; Kafizas,A; Grätzel,M; Piccinin,S; Durrant,JR (J Am Chem Soc, 2026)
Despite its central role in photoelectrochemical (PEC) water splitting, the mechanistic pathway of water oxidation on metal oxides remains unresolved, with population-based and Butler-Volmer (BV) models offering distinct views on how surface valence band holes drive the reaction. Here, we bring together these two perspectives by combining operando photoinduced absorption (PIA) spectroscopy with photocurrent analyses on α-Fe2O3 (hematite) photoanodes as a function of light intensity. We find a crossover from population-controlled, rate law water oxidation at low hole densities to a BV-like, potential driven regime at high densities, triggered by band edge unpinning once surface M-OH species are fully oxidized, and excess holes accumulate without compensation. This mechanistic transition unifies competing models of interfacial charge transfer and reveals design principles for optimizing water oxidation in metal oxide photoelectrodes.